2016
DOI: 10.4236/ojtr.2016.43009
|View full text |Cite
|
Sign up to set email alerts
|

Sling Suspension Therapy Utilization in Musculoskeletal Rehabilitation

Abstract: The development of an effective and inexpensive device to restore and enhance the human musculoskeletal functions is of particular interest. Sling exercise therapy (SET) is one of the most effective developed tools in rehabilitation of musculoskeletal disorders, which has been successfully used in various applications ranging from diagnosis to treatment. To the best of our knowledge, SET has never been comprehended and reviewed previously. Therefore, it was highly required to further understand the role of SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Pain decrease was more evident in the SST group (p = 0.013) as compared to the GBE group. This result is supported by previous research, which has demonstrated the effectiveness of sling suspension therapy in reducing back pain and improving activation of local spinal stabilizers [9,15]. Chronic pain frequently leads to abnormal posture [16], which can be defined as an imbalance between muscle groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Pain decrease was more evident in the SST group (p = 0.013) as compared to the GBE group. This result is supported by previous research, which has demonstrated the effectiveness of sling suspension therapy in reducing back pain and improving activation of local spinal stabilizers [9,15]. Chronic pain frequently leads to abnormal posture [16], which can be defined as an imbalance between muscle groups.…”
Section: Discussionsupporting
confidence: 81%
“…The SST program consisted of open and closed kinetic chain exercises aiming to stabilize and activate trunk muscles using single and multi-point suspension [9].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, sensorimotor exercise on an unstable support surface leads to muscles tone restoration and redistribution, improvement of the harmony of neuromuscular reflexes reactions, and increasing the sensory feedback. As a result, balance is restored by increasing of the motor system response, co-contraction levels, and joint stability [26]. In fact, the MFSST promotes proprioceptive function and develops overall coordination of sensorimotor systems, that all together have a positive impact on postural stability and balance.…”
Section: Discussionmentioning
confidence: 99%